The Tales of Sultan Mehmed, Son of Bayezid Khan [Ahval-i Sultan Mehemmed bin Bayezid Han] : annotated English translation, Turkish edition, and facsimiles of the relevant folia of Bodleian Marsh 313 and Neşri Codex Menzel = Bayezid Han Oğlu Sultan Mehmed’in maceraları [Ahval-i Sultan Mehemmed bin Bayezid Han] : İngilizce tercüme, tenkitli metin, Bodleian Marsh 313 ve Neşri Codex Menzel’in tıpkıbasımları ([Harvard])
xii, 176 s.